PENJATUHAN PIDANA TERHADAP PELAKU PENCURIAN HASIL PERKEBUNAN - Baene, Windasari (Jurnal Panah Hukum, 2024)
Criminal imposition is another word for punishment as a legitimate effort based on law to inflict suffering. Theft is a criminal act of taking something, part or all of which belongs to another person, with the intention of possessing it against the law. One of the criminal acts of theft that has been investigated and tried by the District Court is decision number 569/Pid.Sus/2022/PN.Stb. In this decision, the perpetrator was sentenced to 8 (eight) months in prison for violating article 107 letter d of Republic of Indonesia Law Number 39 of 2014 concerning plantations Jo article 55 paragraph (1) 1 of the Criminal Code and the type of research used by the author is normative research using the statutory regulatory approach, case method, analytical approach. Data collection was carried out using secondary data, which was obtained through library materials consisting of primary materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on research findings and discussions as in the judge's decision, the defendant was sentenced to Article 107 letter d of the Law of the Republic of Indonesia Number 39 of 2014 concerning Jo plantations, Article 55 paragraph (1) 1 of the Criminal Code with a sentence of 8 (eight) months in prison. However, based on the Regulation of the Supreme Court of the Republic of Indonesia Number 02 of 2014 Article 2 paragraph (2) that "If the value of the goods is not more than Rp. 2,500,000.00 (two million five hundred thousand rupiah) the chairman of the court will immediately appoint a single judge to examine, try and decide on the case using a speedy hearing as regulated in Articles 205-210 of the Criminal Procedure Code." So it can be concluded that the criminal sentence in this decision is not appropriate based on the Supreme Court of the Republic of Indonesia Regulation Number 02 of 2012 article 2 paragraph (2), the defendant should not have been detained by the head of the court, applying a single judge to the defendant with a quick examination.